Factors Related to Cognitive Function in Elderly People - Fransiska YD Mardiyanto; Dedeh S Jahja; Yenni Limyati (Journal of Medicine and Health, 2017)
Each year in the world, especially in Indonesia, many elderly people exposed to higher risk of dementia due to an increased number of the elderly population and the incidence of mild cognitive impairment in the elderly. The aim of this study is to find out what factors are related with cognitive function in the elderly population. The study used analytic method with cross sectional study design. Subjects were 60 elderly people; male or female â‰¥ 60 years old. Data were analysed with Chi Square Test (Î± = 0.05). Cognitive function was measured by MMSE test. The result were found a significant relation between age and cognitive function ( p = 0.014), level of education and cognitive function (p value = 0.000), physical activity and cognitive function (p value = 0.003), cognitive activity and cognitive function (p value = 0.002), and social interaction and cognitive function (p value = 0.000). Gender variable did not have relation with cognitive function (p value = 0.343). This study conclude that there was a relation between age, education level, physical activity, cognitive activity and social interaction with cognitive function in the elderly population. There was no relation between gender and cognitive function in the elderly population.Keywords: cognitive function, cognitive impairment, elderly, MMSE